Recent sedimentation rate and sediment ages determination of Kemaman-Chukai mangrove forest, Terengganu, Malaysia - Yunus, Kamaruzzaman; Ong, Meng Chuan (Science Publications, 2008)
Two 20 cm sediment cores were collected with a D-section corer in the Kemaman-Chukai mangrove forest and analyzed for 210Pbex (excess 210Pb) in order to understand the sedimentation pattern. The activities of 210Pb along with the 208Po tracer were measured by Alpha Spectrometry on a silicon surface barrier detector connected to a multi channel analyzer. Sedimentation rates were determined applying 210Pb dating method and found to vary between 0.94-1.11 cm year-1. The highest accumulation rates were recorded near the river mouth and the lowest rates at the downstream. Assuming that the sedimentation rate values are accurate, this implies that the sediments in the upper 100 cm at Kemaman-Chukai mangrove forest were deposited during the past 90 years ago.